Influence of Project-Based Learning Models on Students' Physics Knowledge and Critical Thinking Skills: Meta Analysis - Febrianti, Feby; Asrizal, Asrizal; Emiliannur, Emiliannur (Universitas Negeri Padang, 2023)
Education is expected to be able to improve students' knowledge and critical thinking skills. The first real condition in the field shows that students' skills in the knowledge aspect are in the low category and the second real condition shows that students' skills for critical thinking are low. The solution given to the gap that exists in real conditions and ideal conditions is to apply a project-based learning model to the classroom learning process. The aim of this research is to investigate the influence of the project-based learning model on students' physics knowledge and critical thinking skills, as well as investigate its influence on each variable at grade level. The research method used in this research is meta analysis. The sample from this research was 29 articles. The data analysis technique used in this research uses effect size calculations from each article. The research results show that there is a significant influence of the project-based learning model on the knowledge aspect skills and critical thinking skills, where the calculated effect size values obtained are 1.161 and 0.632. Data from hypothesis testing on each variable at class level, namely class X and XI. The results of hypothesis testing for both class X and class The results of hypothesis testing for critical thinking skills at grade level show that the project-based learning model does not have a significant positive influence on class X students, or the p>α value. Data from hypothesis testing for class XI shows that there is a significant positive influence of the project-based learning model on critical thinking skills, where the p value <α.